Gauging the Impact of Openness on Sustainable development in Nigeria: Evidence from FM-OLS and ARDL approaches to Cointegration - Jimoh Sina OGEDE; Hammed O Tiamiyu (Sriwijaya Journal of Environment, 2022)
This paper considers the nexus between trade openness and sustainable development in Nigeria from 1996 to 2019 by employing Fully Modified Least Square (FMOLS) and Autoregressive Distribution Lags (ARDL) techniques. Our results suggest that trade openness has a significant positive impact on sustainable development and is Nigeria's economic pillar of sustainability. The paper also reveals a significant disparity in magnitude and sign of the parameters when ARDL is used. In the long run, openness to trade has a significant positive impact on sustainable development in Nigeria, implying that an increase in trade openness will improve sustainable development in Nigeria. The effect of the age dependency ratio is insignificant inverse, showing that it does not affect sustainable development. Furthermore, in the short run, except for trade openness and age dependence ratio that has a significant effect, all other independent variables are not statistically significant. The paper concludes that trade openness positively impacts sustainable development in Nigeria. The paper's hypothesis is likely to trigger a fresh conversation on how to promote sustainable development and so mitigate environmental risks.